The Phonetics and Phonology of Regional English Accents: A Study - T. Prakash (ILN Journal: Indian Literary Narratives, 2025)
This study explores the phonetics and phonology of regional accents in English, aiming on how distinctions in pronunciation impact intelligibility, identity, and linguistic acuity. English, as a global language, displays significant regional variances in phonetic articulation and phonological patterns, molded by historical, social, and geographical influences. By examining vital phonetic features such as vowel shifts, consonant variations, and prosodic patterns, this research surveys prominent English accents, including Received Pronunciation (RP), General American (GA), Cockney, African American Vernacular English (AAVE), and Australian English. The study employs acoustic analysis and sociolinguistic analyses to explore how these accents differ in articulation, rhythm, and stress patterns. Additionally, it explores how phonological dissimilarities impact language conception and social uniqueness among speakers and listeners. The findings offer intuitions into the role of accent perception in communication and its allegations for English language teaching, speech recognition technology, and linguistic diversity consciousness. This research gives to a profounder understanding of the vibrant nature of English phonetics and phonology in a gradually interconnected world.